ISLAM DAN GENDER ( Analisis Teks Relasi Gender Dalam Islam) - Triana Sofiani (Muwazah, 2010)
Religion (Islam) as brace of gender gap remains a discourse of the debate in various circles. This happens not because religious texts themselves, but patrarkhi culture that manifest in the reality of daily life affect the interpretation and understanding of religious texts. Gender-biased views and believed that the religious law, as stated by the authoritative texts explicitly and also have the level of sacred like religion, for example: women are created from the rib of men; women as a source of fitna, women less their minds, women's lack of religion; Women should not become a leader; sexuality is an absolute property of men and others